Nature+ in Kenya: Soil baseline report for Kenya - Kaushal, Manoj; Baijukya, Frederick; Gebrehawaryat, Yosef; Fadda, Carlo (2024)
Soil is a dynamic and complex ecosystem that supports a vast array of organisms, including a diverse population of microbes such as bacteria, fungi, actinomycetes, archaea, and protozoa. These microorganisms play a fundamental role in soil health, functioning as the engines behind key ecological processes such as nutrient cycling, organic matter decomposition, soil structure formation, and the regulation of plant pathogens. In agricultural systems, soil microbes are instrumental in enhancing soil fertility by facilitating nutrient uptake by plants, promoting plant growth, and even aiding in the mitigation of soil-borne diseases.